Low temperature plasma polymerization: An effective process to enhance the basalt fibre/matrix interfacial adhesion. (October 2021) - Lilli, Matteo; Zvonek, Milan; Cech, Vladimir; Scheffler, Christina; Tirillò, Jacopo; Sarasini, Fabrizio
Abstract: The interface of fibre reinforced composite materials is deeply affected by the type of sizing applied to the surface of the fibres. In this study, a polymer film based on pure tetravinylsilane (TVS) or its mixture with two different oxygen amounts was deposited on the surface of unsized basalt fibres by plasma enhanced chemical vapor deposition. At first, the influence of the plasma process was investigated through a single fibre tensile test characterization, which did not show any strength degradation of the modified fibres. Subsequently, single fibre pull-out tests were performed to study interfacial strength with an epoxy matrix. The presence of oxygen within the polymer film mixture allowed to increase the interfacial shear strength (IFSS) by 79% compared to untreated basalt fibres, highlighting an excellent fibre/matrix interface for the micro composite. After the interfacial adhesion tests, scanning electron microscopy confirmed the strong bond between the fibre surface and the deposited silane sizing. Highlights: A homogeneous polymeric film was deposited on the surface of unsized basalt fibres through PECVD. Three different sizing mixtures were applied: pure TVS, TVS/52% O2 mixture and TVS/71% O2 mixture. The plasma polymerization process preserved the mechanical properties of the basalt fibres. The TVS/52% O2 mixture enhanced the interfacial adhesion with an epoxy matrix by 79%.